Sosialisasi Pengelolaan Keuangan Keluarga Secara Syariah dengan Pendekatan Gender di Desa Mulyamekar - Suryana, Eka Ahadiyat; Fadhilah, Siti; Khumaira, Nissa Yulia Putri (Melati Institute, 2025)
The majority of people in managing their family finances still use traditional concepts, especially housewives who are now family financial managers and use their finances only for consumption activities. In household life, the wife's role is often dominant in daily financial management, but has not been fully supported by an understanding based on Islamic values. Through an interactive lecture and question and answer approach, the community was introduced to the concept of Islamic finance which emphasizes the principles of justice, transparency, blessings, and the importance of a joint role between husband and wife in financial planning. This socialization activity aims to increase the understanding of the Mulyamekar Village community towards sharia family financial management with a gender approach. The program also educated the community to use sharia-based financial products and develop a healthy and sustainable household budget. The results showed a significant increase in the community's understanding of the basic concepts of sharia finance, the importance of zakat, infaq, and sadaqah, and the implementation of a simple lifestyle. This socialization proves that contextual and gender-based Islamic financial literacy can build collective awareness to create a financially independent family in accordance with Islamic principles.